Design and optimization of wireless in‐situ sensor coupled with gas–water equilibrators for continuous pCO2 measurement in aquatic environments. (12th July 2022) - Lee, Daryl Jia Jun; Kek, Kah Teik; Wong, Wei Wen; Mohd Nadzir, Mohd Shahrul; Yan, Jinpei; Zhan, Liyang; Poh, Seng‐Chee
Abstract: Affordable, highly precise, and accurate CO2 sensor is a prerequisite for more extensive CO2 measurements in various environmental settings, and thus more accurate local and global carbon budgets. Here, we propose the use of an autonomous system for the detection of CO2 concentration (mole fraction), appropriate for inland freshwater and eutrophic coastal environments. We describe the construction of a CO2 sensing device (SIPCO2 ‐II) using off‐the‐shelf commercial products that integrate wireless communication capability. We also report the proof of concept of two newly designed gas–water equilibrators (GWEs) for in‐situ CO2 monitoring to be used with SIPCO2 ‐II. The performance of the SIPCO2 ‐II is evaluated in detail, providing information on the sensor sensitivity, detection limit and stability, and comparing these to a commercially available CO2 analyzer (LGR 915‐0011; Los Gatos Research). Comparison results demonstrate good agreement between the two devices with the root mean square error of 5%. The accuracy and precision of SIPCO2 ‐II against CO2 reference gases are evaluated and values are within 99–104% recovery and 0.9–3 ppm, respectively. The GWEs which comprised either a semi‐passive floater (free‐drifting float equilibrator; FDFE) or a hybrid showerhead‐marble equilibrator (SME) are tested in the laboratory and in the environment. Overall, the SME outperforms FDFE in terms of response time (4 vs. 16 min). The FDFE can cover larger survey areas with lower cost, due to its semi‐passive feature that allows it to drift with water current. The outcome of our study provides an alternative to budget‐constrained CO2 monitoring regimes without compromising the accuracy and precision of the measurements.